Asymptomatic Lymphogranuloma Venereum among Nigerian Men who have Sex with Men. (4th October 2017) - Crowell, Trevor; Hardick, Justin; Lombardi, Kara; Amusu, Senate; Odeyemi, Sunday; Ivo, Andrew; Baral, Stefan; Nowak, Rebecca; Adebajo, Sylvia; Charurat, Manhattan; Ake, Julie; Gaydos, Charlotte
Abstract: Background: Among men who have sex with men (MSM), lymphogranuloma venereum (LGV) has been associated with proctocolitis that can lead to chronic complications and requires a longer course of antibiotic therapy than is recommended for infections due to other serovars of Chlamydia trachomatis (CT). We describe the prevalence and clinical features of LGV among Nigerian MSM diagnosed with anorectal CT. Methods: MSM were recruited into the ongoing RV368 cohort in Lagos, Nigeria, using respondent-driven sampling. Participants were screened for HIV and bacterial sexually transmitted infections (STIs) every three months for up to 18 months. HIV was diagnosed using a parallel algorithm of rapid tests on fingerstick blood samples. PCR testing for Neisseria gonorrheae and CTwas performed on voided urine, oropharyngeal swab, and rectal swab specimens. For this analysis, prevalent and incident cases of rectal CT infection underwent additional testing to identify LGV serovars utilizing novel real-time PCR assays specific for the L serovars of CT Chlamydia trachomatis . Results: From 28 April 2014–19 July 2016, 420 men underwent screening for rectal STIs, including 66 (15.7%) who had prevalent rectal infection with CT. An additional 68 participants developed incident infections during 208 person-years of follow-up. Of 134 eligible rectal swab specimens, 128 underwent further testing for LGV serovars. Seven (5.5%) of the tested samples were identified as LGV serovars of CT. None of the seven participants with LGV reported any symptoms such as fever or rectal pain. Two of the participants with LGV were simultaneously co-infected with rectal gonorrhea. HIV co-infection was common among participants with both LGV and non-LGV serovars of CT (71% and 77%, respectively, P  = 0.74). Conclusion: LGV was uncommon but present among Nigerian MSM in this study. LGV needs to be considered even in asymptomatic cases, particularly if anorectal CT infection fails to respond to the usual course of therapy. Consistent screening for L serovars of CT, or empiric treatment for LGV in cases with a high suspicion for this diagnosis, could potentially improve patient outcomes and decrease transmission. Disclosures: All authors: No reported disclosures.